Barr Bodies Revelation from Dental Pulp – A Comparative Study on the Basis Of X- Chromatin Visibility and Nuclear Membrane Clarity - Bhardwaj, Nandini; Bhat, Nitish; Wadhwan, Vijay; Khangura, Amberpreet Kaur; puri, Abhiney; Yasothkumar, Dinesh (Journal of Neonatal Surgery, 2025)
Background: A convex or triangular shaped dynamic inactivated X chromosomal configuration is seen in female somatic cell nuclei. These morphologic variants are termed as Sex chromatin or barr bodies. Determination of gender is of valuable significance especially in cases where bodies are charred/ burnt and are beyond positive identification. Discovered by Murray Barr, these bodies are inactivated by a process known as Lyonization. Dental pulp, blood, hair follicles buccal smears etc proves to be impending sources from which barr bodies can be obtained. Aims and objectives: The main aim and objective of the study is to assess barr bodies on the basis of X- chromatin visibility and nuclear membrane. Intraobserver variability of barr bodies were also evaluated and both histopathological and cytopathological methods were also evaluated Material and methods: Total number of 60 subjects i.e. extracted teeth within the age group 10-40 years from 20 male & 40 females were taken. Dental pulp was obtained from the extracted teeth. Total number of two respective groups, Group 1 and Group II were categorized which included 10 males & 20 females each. Rapid tissue processing was done in group I and in Group II cytological method using centrifugation was inculcated. Results: Nuclear membrane was extremely noticeable in rapid tissue processing histopathological method samples both in males and females. Conversely, in cytological method, the clarity of membrane was very indistinct. In Histopathological females of group 1, X-chromatin visibility was of paramount excellence. In case of males of both group I and II, X- chromatin was poorly visualized. A statistically significant difference was obtained Conclusion: Nuclear membrane and X- chromatin visibility were superior in histopathological method especially in case of females. Histopathological method was found to be more feasible in revelation of barr bodies for medico- legal purposes